Study on acceptance level of online education during pandemic period among under graduate and post graduate students - Sarguroh Sonde, Nazneen Ebrahim (Technium Social Sciences Journal, 2022)
This study focuses on analysing the acceptance level with the online education among under graduate and post graduate students during period of pandemic especially during Covid-19. In this regard, student perception with the online education was analysed using the secondary data as collected from various sources. As the COVID-19 pandemic threatens the academic calendars, educational institutions around the world have been closed and about 70% of the students are engaged in the online education. Students faced various problems related to depression, poor internet activity and inconvenient home learning environment. The online education by the various e-techniques and methods has proven to a solution for colleges and universities, but still the success of online education depends on student’s perception and satisfaction level. The sudden transition from a face-to-face to virtual space causes a disruption to the students. Based on the findings of these study, the research implications for educational institutions and researchers are discussed.